Mencegah HIV & AIDS Sejak Dini Demi Generasi Cemerlang, “SAPE” Safe, Aware, Prevention, and Education - Islami, Vita Hani; Aminah, Aminah; Umaimah, Anisa; Jaizzur, Akhmad (Universitas Pahlawan Tuanku Tambusai, 2026)
HIV and AIDS remain global health issues that have a significant impact on adolescents, who are in a vulnerable phase to engage in risky behaviors. A health promotion activity with the theme